THE VISUALITY OF MODERN LITHUANIAN CHILDREN’S BOOKS: READERS’ AND PUBLISHERS’ APPROACH - KATINAITĖ, KAROLINA (Knygotyra, 2014)
This paper examines a new trend in society, namely the phenomenon of visual culture. Its influence is also felt in the publishing industry. Firstly, the article discusses the classification of children’s books by age groups as well as the importance of the book as an educational measure from the very early infancy. The main aim of the article is to analyse readers’ and publishers’ approaches to the visuality of Lithuanian children’s books. The following tasks were set to achieve this aim: to create target questionnaires for readers and publishers; assess adults’ (as buyers and readers) opinion about the visual impact of children’s books; ascertain the views of publishers on children’s books visuality, their criteria for design, illustration and printing. The research part of the paper combines readers’ and publishers’ approach to visual issues in the books for children. The empirical study was composed of the following two structural elements: a questionnaire method applied to the readers, and an interview method applied to the publishers. Readers are characterized as buyers of books (parents or other mature people who can afford buying a book). The research targeted at publishers covered the following organizations: “Nieko rimto”, “Dominicus Lituanus” and “Presvika”. In conclusion, the survey revealed that the approach of both readers and publishers is very similar on many issues. Thus, the need for children education using books since early infancy has been identified during the research. Furthermore, most publishers offer books in the market for all age groups including infants. As it is written in multiple scientific sources, respondents also perceive the importance of books in a child’s educational process. It is a well-known fact that books develop the body motility and linguistic skills: they also help meet the cognitive needs. Besides, a book is also regarded as a great communication tool. It has been established that the visual aspects are highly considered when choosing and buying a book for children. Both readers and publishers emphasize the importance of harmony in the book, when all elements, included content, design, layout, illustrations, are in harmony with each other. Readers tend not to buy the books, which do not satisfy one of the required elements (content-related or visual quality) However, both readers and publishers are glad about the general situation of publishing industry in Lithuania. A high quality of printing, creative authors and illustrators are the features of the today’s market.